Effects on quality in audio steganography - Ho, Man Yen (2014)
This thesis focuses on effects on quality in audio steganography. Steganography is the science of hiding information, which is used to hiding the data from third party. Audio Steganography is a technique used to transmit hidden information by modifying an audio signal in an imperceptible manner. Embedding information into audio steganography is more secure due to less steganalysis techniques for attacking to audio. Least significant bit (LSB) coding is the simplest way to embed information in a digital audio file. By substituting the least significant bit of each sampling point with a binary message, LSB coding allows for a large amount of data to be encoded. Listening test and SNR will be carry out to test the quality between original file and embedded file. The payload can affect the quality of sound. Thus, it can said that LSB method can embed high payload of hidden message compare to other methods. Besides, different LSB position can also affect the quality of audio. The experimental result of this research is that the secret message can be hidden up to LSB position 3 to maintain imperceptible for the audio sound.